From Traditional to Digital: A Mini Review on Flipped Classroom in Mathematics Education - Amelia Defrianti Putri; Dadang Juandi; Margaretha Madha Melissa; Dilham Fardian; Al Jupri; Turmudi Turmudi (SJME (Supremum Journal of Mathematics Education), 2026)
The flipped classroom is an instructional innovation that has been increasingly implemented in mathematics education. This model transforms traditional instruction by delivering learning materials outside the classroom through videos or reading resources, while class time is devoted to interactive activities such as discussion and problem solving. This mini-review aims to analyze the implementation of the flipped classroom in mathematics education, its impact on student engagement and learning outcomes, the challenges encountered, and strategies for effective implementation. The study adopts a mini-review approach with a systematic study selection process. Articles were retrieved from Scopus, Web of Science, and Google Scholar, covering publications from 2015 to 2024. Of the 134 articles identified, 27 studies were selected through title, abstract, and full-text screening. The findings indicate that flipped classroom implementation varies across educational levels. At the primary level, its effectiveness depends on scaffolding and adult support, whereas at the secondary and higher education levels, the flipped classroom enhances student engagement, conceptual understanding, and learning outcomes, despite challenges related to self-regulated learning readiness and unequal access to technology. Compared to traditional instruction, the flipped classroom emphasizes learner autonomy, in-class problem-solving activities, and the use of digital technologies, while requiring strong instructional design and institutional support to be effective.